2003
DOI: 10.1161/01.cir.0000092886.52404.50
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone Reduces the Accelerated Neointima Formation After Arterial Injury in a Mouse Injury Model of Type 2 Diabetes

Abstract: Background-Hyperglycemia (HG) and hyperinsulinemia (HI) may be factors enhancing the atherosclerotic complications of diabetes. We hypothesized that specific feeding of C57BL/6 apolipoprotein (apo) E Ϫ/Ϫ mice would alter their metabolic profiles and result in different degrees of neointima (NI) formation. We additionally hypothesized that an insulin-sensitizing agent (rosiglitazone) would prevent the development of type 2 diabetes and reduce neointima formation after carotid wire injury measured at 28 days. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 39 publications
4
43
0
5
Order By: Relevance
“…We and others have previously reported that atherosclerosisprone apoE-deficient (apoE Ϫ/Ϫ ) mice develop severe hypercholesterolemia, accelerated atherosclerosis, significant insulin resistance, and hyperglycemia when fed an atherogenic Western diet (WD). [17][18][19] The present study further showed that WD-fed apoE Ϫ/Ϫ mice developed high levels of plasma sCD40L as well as exaggerated neointima formation after carotid wire denudation injury compared with chow-fed apoE Ϫ/Ϫ mice. Therefore, this model provides a unique opportunity for understanding the role of elevated circulating CD40L in neointima formation after vascular injury under clinically relevant conditions.…”
supporting
confidence: 69%
“…We and others have previously reported that atherosclerosisprone apoE-deficient (apoE Ϫ/Ϫ ) mice develop severe hypercholesterolemia, accelerated atherosclerosis, significant insulin resistance, and hyperglycemia when fed an atherogenic Western diet (WD). [17][18][19] The present study further showed that WD-fed apoE Ϫ/Ϫ mice developed high levels of plasma sCD40L as well as exaggerated neointima formation after carotid wire denudation injury compared with chow-fed apoE Ϫ/Ϫ mice. Therefore, this model provides a unique opportunity for understanding the role of elevated circulating CD40L in neointima formation after vascular injury under clinically relevant conditions.…”
supporting
confidence: 69%
“…Macrophage infiltration into the expanding neointima was also reduced by this intervention. 52 Note that these studies are in contradistinction to those of Levi et al 39 with respect to the effect of rosiglitazone on hyperglycemia. Specifically, in Levi's studies, apo EϪ/Ϫ mice were made frankly diabetic by relative deficiency of insulin using streptozotocin; 39 in the Phillips studies, hyperglycemia was induced by feeding Western diet, thereby causing insulin resistance.…”
Section: Diabetes and Restenosis: Other Models And Distinct Interventmentioning
confidence: 76%
“…Phillips et al used Western diet-fed apo EϪ/Ϫ mice to show that these mice develop insulin-resistant diabetes; administration of rosiglitazone prevented the development of hyperglycemia and hyperinsulinemia. 52 In parallel, neointimal expansion was reduced by 65% after arterial injury in Peroxisome proliferator-activated gamma agonist (rosiglitazone) versus vehicle-fed apo EϪ/Ϫ mice. Macrophage infiltration into the expanding neointima was also reduced by this intervention.…”
Section: Diabetes and Restenosis: Other Models And Distinct Interventmentioning
confidence: 95%
“…ApoE KO mice fed a WD exhibit a metabolic phenotype consistent with T2D, which includes elevated insulin and glucose levels as compared with standard chow-fed mice (28)(29)(30). During the 12-week time period, mice were injected intraperitoneally every 3 days with either vehicle peptide or CavNOxin (2.5 mg/kg).…”
Section: Experimental Designmentioning
confidence: 99%